Treatment planning for cardiac radioablation: multicenter multiplatform benchmarking for the RAdiosurgery for VENtricular TAchycardia (RAVENTA) trial : physics contribution - Kluge, Anne; Ehrbar, Stefanie; Grehn, Melanie; Fleckenstein, Jens; Baus, Wolfgang W.; Siebert, Frank-Andre; Schweikard, Achim; Andratschke, Nicolaus; Mayinger, Michael C.; Boda-Heggemann, Judit; Bürgy, Daniel; Celik, Eren; et al. (International journal of radiation oncology, biology, physics, 2022)
Purpose - Cardiac radioablation is a novel treatment option for patients with refractory ventricular tachycardia unsuitable for catheter ablation. The quality of treatment planning depends on dose specifications, platform capabilities, and experience of the treating staff. To harmonize the treatment planning, benchmarking of this process is necessary for multicenter clinical studies such as the RAdiosurgery for VENtricular TAchycardia trial. - Methods and Materials - Planning computed tomography data and consensus structures from 3 patients were sent to 5 academic centers for independent plan development using a variety of platforms and techniques with the RAdiosurgery for VENtricular TAchycardia study protocol serving as guideline. Three-dimensional dose distributions and treatment plan details were collected and analyzed. In addition, an objective relative plan quality ranking system for ventricular tachycardia treatments was established. - Results - For each case, 3 coplanar volumetric modulated arc (VMAT) plans for C-arm linear accelerators (LINAC) and 3 noncoplanar treatment plans for robotic arm LINAC were generated. All plans were suitable for clinical applications with minor deviations from study guidelines in most centers. Eleven of 18 treatment plans showed maximal one minor deviation each for target and cardiac substructures. However, dose-volume histograms showed substantial differences: in one case, the planning target volume ≥30 Gy ranged from 0.0% to 79.9% and the ramus interventricularis anterior V14Gy ranged from 4.0% to 45.4%. Overall, the VMAT plans had steeper dose gradients in the high-dose region, while the plans for the robotic arm LINAC had smaller low-dose regions. Thereby, VMAT plans required only about half as many monitor units, resulting in shorter delivery times, possibly an important factor in treatment outcome. - Conclusions - Cardiac radioablation is feasible with robotic arm and C-arm LINAC systems with comparable plan quality. Although cross-center training and best practice guidelines have been provided, further recommendations, especially for cardiac substructures, and ranking of dose guidelines will be helpful to optimize cardiac radioablation outcomes.